Fibrous hamartoma of infancy: A case report with typical ultrasonographic findings - Demirtaş-Güner, Duygu; Susam-Şen, Hilal; Akçören, Zuhal; Yalçın, Bilgehan; Oğuz, Berna; Akyüz, Canan (The Turkish Journal of Pediatrics, 2016)
Fibrous hamartoma of infancy (FHI) is a rare, benign lesion which is commonly seen under two years of age. Clinical and radiological features of FHI can mimic malignant soft tissue sarcomas, it is important to make differential diagnosis. Ultrasound (US) examination reveals heterogeneous echogenicity that can be also suggestive for other soft tissue tumors but newly defined "serpentine pattern" of intervening hypoechoic portions in the hyperechoic mass with poorly defined margins and with poor vascularity is special for FHI. Here we report a 15-month-old-boy with FHI with serpentine pattern on US. He initially presented with a painless mass in his left axilla existing for approximately seven months. The mass was successfully excised and he has been followed for three years without any evidence of recurrence. Fibrous hamartoma of infancy should always be considered in differential diagnosis in children under two years of age with a firm and solitary mass in the axilla especially when US reveals serpentine pattern with poorly defined margins and with poor vascularity. If these clinical and ultrasonographic findings are seen in a child under two years old, surgery can be performed without any additional imaging modalities. Awareness and careful assessment are important in order not to misdiagnose this benign mass for which surgical excision is curative.